PERLINDUNGAN KONSUMEN ATAS OBAT SIRUP ANAK YANG TERCEMAR ETILEN GLIKOL (EG) DAN DIETILEN GLIKOL (DEG) YANG MELEBIHI AMBANG BATAS AMAN - NIM. A1011191123, TANIA YOGA PUTRI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractConsumer protection is a legal instrument used to protect and fulfill consumer rights. Recently, the people of Indonesia have been shocked by cases of acute kidney failure that have affected hundreds of children aged 0